2008
DOI: 10.1086/592263
|View full text |Cite
|
Sign up to set email alerts
|

Electrodynamics of Magnetars. III. Pair Creation Processes in an Ultrastrong Magnetic Field and Particle Heating in a Dynamic Magnetosphere

Abstract: We first examine the QED processes that create electron-positron pairs in magnetic fields approaching and exceeding 10 14 G. The formation of free and bound pairs is addressed, and the importance of positronium dissociation by thermal X-rays is noted. We calculate the collision cross section between an X-ray and a gamma ray, and point out a resonance in the cross section when the gamma ray is close to the threshold for pair conversion. We then show how the pair creation rate in the open-field circuit and the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 80 publications
3
32
0
Order By: Relevance
“…High‐multiplicity cascades due to RICS may still occur along twisted lines in the closed‐field region (where the primary electrons never reach Lorentz factors larger than γ 0 ∼10 3 ), as they do in magnetars (e.g. Thompson et al 2002; Beloborodov & Thompson 2007; Thompson 2008a,b; Beloborodov 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High‐multiplicity cascades due to RICS may still occur along twisted lines in the closed‐field region (where the primary electrons never reach Lorentz factors larger than γ 0 ∼10 3 ), as they do in magnetars (e.g. Thompson et al 2002; Beloborodov & Thompson 2007; Thompson 2008a,b; Beloborodov 2009).…”
Section: Discussionmentioning
confidence: 99%
“…More recently it has been suggested that the pair cascade is also necessary for non‐thermal emission from magnetars (e.g. Beloborodov & Thompson 2007; Thompson 2008a,b; see Woods & Thompson 2006 for a review of magnetars). The basic pair cascade involves several steps: (i) acceleration of primary particles by an electric field parallel to the magnetic field; (ii) gamma‐ray emission by the accelerated particles moving along the magnetic field lines (either by curvature radiation or by inverse Compton upscattering of surface photons); (iii) field‐assisted photon decay into electron–positron pairs as the angle between the photon and the magnetic field line becomes sufficiently large, or pair production by two‐photon annihilation in weak‐field regimes; (iv) gamma‐ray emission by the newly created particles as they lose their transverse energy through synchrotron emission; (v) further pair production and gamma‐ray emission via steps (iii) and (iv).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Creation of electron-positron pairs is predicted to be triggered in a variety of ways: in intense electromagnetic backgrounds such as two plane waves propagating in different directions [16,17], in a similar setup with the inclusion of the Coulomb field of a nucleus [18], but also in more exotic contexts, such as photons decaying in magnetic fields of magnetars [19]. Another example is through thermal radiation, with pair-creation rates having been calculated in a constant electric field in various formalisms [20][21][22], also including stimulated pair creation [23].…”
Section: Introductionmentioning
confidence: 99%